FACTORS AFFECTING FEED INTAKE IN CULTURED FISH SPECIES: A REVIEW - Eriegha, Ochuko Joshua; Ekokotu Paterson Adogbeji (Animal Research International, 2017)
Feed expense constitutes the bulk of the whole cost of production in any intensive aquaculture setup in Nigeria. Consequently, feed and feeding stratagems are of paramount interest for feed utilization as well as profit maximization. However, the paucity of documents on the factors affecting feed intake in cultured fish is negatively influencing the efficiency of fish production from aquaculture. Hence, the major factors influencing feed intake by cultured fish are discussed. These factors include management practices, environment conditions, feed quality, inherent genetic factor and physiological condition of the fish. The review would help to increase basic knowledge on the nutrition (with emphasis on feed intake) of aquaculture species for improved management and productivity.
Keywords: Nutrition; Aquaculture environment; Fish metabolism; Feed management; Feed quality; Feed intake